Pengaruh Pemberian Pakan Alami Dan Pakan Buatan Terhadap Pertumbuhan Benih Ikan Betutu (Oxyeleotris marmorata bleeker)Pengaruh Pemberian Pakan Alami Dan Pakan Buatan Terhadap Pertumbuhan Benih Ikan Betutu (Oxyeleotris marmorata bleeker) [The Influence Of Giving Natural Feed And Make Feed To Growth Fingerlings Of Betutu (Oxyeleotris marmorata bleeker)] - Muhammad Arief; Irmaya Triasih; Widya Paramita Lokapirnasari (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
Abstract The growth of betutu classified slow, so do efforts in order that growth of betutu which protected optimal by choosing the exact food combination. This research is purpose to know the growth fingerlings of betutu. This research using complete random program giving 3 repeated by the way of treating P1 (food 100% pelet), P2 (food 100% Daphnia spp.), P3 (food 100% Tubifex sp.), P4 (food 100% Anadara granosa), P5 (food combination 50% pelet and 50% Daphnia spp.), P6 (food combination 50% pelet and 50% Tubifex sp.), P7 (food combination 50% Anadara granosa and 50% Daphnia spp.), P8 (food combination 50% Anadara granosa and 50% Tubifex sp.). Main test parameter checked on this research is growth (accretion weight), growth rate, specific growth rate, and absolute body length growth, while supporting test parameter is water quality. Data of growth analysis using ANAVA (varian analysis) and if there is the influence the way of treating so continued with Test of Multiple Gap Duncan by trusty degree 95%. The result of research show the growth (accretion weight), growth rate, specific growth rate and the best absolute body length growth on the way of treating P6 which not different with the way of treating P3 and P8.